Development of Mathematics E-LKPD with STEM Approach on Linear Program Materials - Khotimah, Khusnul; Arina, Setia Dwi; Wardani, Dian Kusuma; Umardiyah, Fitri (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
This research is a type of development research or R&D (Research and Development) which aims to determine the process and results of the development of E-LKPD mathematics with a science, technology, engineering, and mathematics (STEM) approach of linear program materials. The development model in this study uses the ADDIE model. Based on the results of the validity data analysis, according to the assessment of media experts, a percentage of 93.42% was obtained with a very valid category, and from material experts a percentage of 90.63% with a very valid category. The results of the students' responses increased the percentage to 85.86% with a very practical category. The results of the learning percentage obtained from the post test were 81% greater than the results of the learning percentage obtained from the results of the pre-test. Based on these data, it can be concluded that E-LKPD mathematics with a STEM approach for linear program materials is valid, effective and practical.